Melatonin Induced Cold Tolerance in Plants: Physiological and Molecular Responses - Qari, Sameer H.; Hassan, Muhammad Umair; Chattha, Muhammad Umer; Mahmood, Athar; Naqve, Maria; Nawaz, Muhammad; Barbanti, Lorenzo; Alahdal, Maryam A.; Aljabri, Maha (Frontiers in Plant Science, 2022)
Cold stress is considered one of the limiting factors for plants growth and development. Cold stress adversely affects the plant physiology, molecular and biochemical processes by inducing oxidative stress, poor nutrient and water uptake, disorganization of cellular membranes and reduced photosynthetic efficiency. Therefore, to improve the plant's performance in cold stress, the application of bio-stimulants is considered an imperious strategy. Melatonin (MT) is a critical bio-stimulant that enhances the plant's performance under cold stress. Melatonin application improved the plant growth and tolerance to cold stress by maintaining membranes integrity, plant water contents, stomatal movements, photosynthetic efficiency, nutrient and water uptake, redox homeostasis, osmolytes, hormones and secondary metabolites accumulation and scavenging the reactive oxygen species (ROS) through improved antioxidant activities and increase in expression of stress-responsive genes. Thus, it is essential to understand the mechanisms of MT induced cold tolerance and identify the diverse research gaps that must be answered in future research programs. This review discussed the MT involvement to control various physiological and molecular responses for inducing cold tolerance. We also shed light on engineering MT biosynthesis for improving the cold tolerance in plants. Moreover, we highlighted areas where future research is needed to make it a vital antioxidant to confer cold tolerance in plants.